Antioxidant activity of white rice, brown rice and germinated brown rice (in vivo and in vitro) and the effects on lipid peroxidation and liver enzymes in hyperlipidaemic rabbits - Mohd Esa, Norhaizan; Abdul Kadir, Khairul Kamilah; Amom, Zulkhairi; Azlan, Azrina (Elsevier, 2013)
Antioxidant activity of different rice extract and the effect on the levels of antioxidant enzyme activity, superoxide dismutase (SOD) and glutathione peroxidase (GPx), vitamin E, lipid peroxidation and liver enzymes in hyperlipidaemia rabbits were investigated. Germinated brown rice (GBR) has the highest antioxidant activity compared to white rice (WR) and brown rice (BR). All rice grains increased the activity of SOD and GPx. However, vitamin E levels increased only in the groups that received the BR and GBR diets. The reduction of lipid peroxidation levels and activity of hepatic enzymes (alanine transferase, ALT and aspartate transaminase, AST) were only significantly observed in the GBR group. In conclusion, GBR supplementation has the greatest impact on increasing antioxidant enzyme activity and vitamin E level and on reducing lipid peroxidation in hypercholesterolaemia rabbit, thereby preventing the formation of atherosclerotic plaques. Furthermore, GBR diet can also reduce the level of hepatic enzymes.